Vascular permeability in cancer and infection as related to macromolecular drug delivery, with emphasis on the EPR effect for tumor-selective drug targeting - MAEDA, Hiroshi (The Japan Academy, 2012)
Tumor and inflammation have many common features. One hallmark of both is enhanced vascular permeability, which is mediated by various factors including bradykinin, nitric oxide (NO), peroxynitrite, prostaglandins etc. A unique characteristic of tumors, however, is defective vascular anatomy. The enhanced vascular permeability in tumors is also distinctive in that extravasated macromolecules are not readily cleared. We utilized the enhanced permeability and retention (EPR) effect of tumors for tumor selective delivery of macromolecular drugs. Consequently, such drugs, nanoparticles or lipid particles, when injected intravenously, selectively accumulate in tumor tissues and remain there for long periods. The EPR effect of tumor tissue is frequently inhomogeneous and the heterogeneity of the EPR effect may reduce the tumor delivery of macromolecular drugs. Therefore, we developed methods to augment the EPR effect without inducing adverse effects for instance raising the systemic blood pressure by infusing angiotensin II during arterial injection of SMANCS/Lipiodol. This method was validated in clinical setting. Further, benefits of utilization of NO-releasing agent such as nitroglycerin or angiotensin-converting enzyme (ACE) inhibitors were demonstrated. The EPR effect is thus now widely accepted as the most basic mechanism for tumor-selective targeting of macromolecular drugs, or so-called nanomedicine.